2000
DOI: 10.1097/00006454-200012000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Serious adverse events after measles-mumps-rubella vaccination during a fourteen-year prospective follow-up

Abstract: Causality between immunization and a subsequent untoward event cannot be estimated solely on the basis of a temporal relation. Comprehensive analysis of the reported adverse reactions established that serious events causally related to MMR vaccine are rare and greatly outweighed by the risks of natural MMR diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 39 publications
(1 reference statement)
4
70
0
4
Order By: Relevance
“…* Based on previously described analysis. 25 The immediate or nonimmediate allergic reactions of 36 vaccinees with serum samples available were further evaluated, with 18 cases of suspected anaphylaxis, 13 of urticaria (5 cases accompanied by angioedema and 1 by asthmatic symptoms), 4 of asthmatic symptoms, and 1 of Henoch-Schö nlein purpura. The characteristics of these 36 participants are presented in Tables 1 and 2, and their histories of allergy are summarized in Tables 3 and 4. Of these 36 reactions, 25 (69.4%) occurred after the first dose of MMR vaccine and 10 (27.8%) after the second dose; in 1 case this information was lacking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…* Based on previously described analysis. 25 The immediate or nonimmediate allergic reactions of 36 vaccinees with serum samples available were further evaluated, with 18 cases of suspected anaphylaxis, 13 of urticaria (5 cases accompanied by angioedema and 1 by asthmatic symptoms), 4 of asthmatic symptoms, and 1 of Henoch-Schö nlein purpura. The characteristics of these 36 participants are presented in Tables 1 and 2, and their histories of allergy are summarized in Tables 3 and 4. Of these 36 reactions, 25 (69.4%) occurred after the first dose of MMR vaccine and 10 (27.8%) after the second dose; in 1 case this information was lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Egg allergy was present in 1 child, who had asthmatic symptoms 24 hours postvaccination, but his serology was positive for concurrent Moraxella catarrhalis infection. 25 Two children with urticaria and 1 with anaphylaxis had outgrown their egg sensitivity. Asthma had been previously diagnosed in 2 individuals with anaphylaxis, 1 with asthmatic symptoms, and 1 with urticaria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large population-and ecologic-based studies were conducted over the following decade that consistently found no evidence of a link between the MMR vaccine and autism and failed to provide any support for Wakefield's theory [24][25][26][27]. In fact, the lack of an association between MMR vaccination and autism in children is supported by 19 additional scientific studies performed by diverse groups of investigators using various research methodologies involving disparate groups of patients over more than a decade [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Several of these studies have been discussed in detail in 4 review articles [47][48][49][50].…”
Section: Lack Of Evidence To Support the "Mmr Causes Autism" Theorymentioning
confidence: 99%
“…49 Although a group of investigators in the United Kingdom has hypothesized that administration of the measles-mumps-rubella (MMR) vaccine was associated with an increased risk of ASD, 50 this hypothesis has not been substantiated by more in-depth research. 46,[51][52][53][54][55] ASD and autistic behaviors are seen at an increased rate in persons with a number of genetic, chromosomal, and metabolic disorders, such as tuberous sclerosis, fragile X syndrome, duplication of 15q 11-13, 56 methylmalonicaciduria, and untreated phenylketonuria.…”
Section: Neurogenetic Correlates Of Asdmentioning
confidence: 99%